Confidence Charms: How Superstition Influences Overconfidence Bias in Han and the Qiang Ethnic Minority Chinese. Issue 5 (17th June 2021) - Li, Heng
Abstract: The overconfidence effect is a cognitive bias in which individuals' subjective confidence in their judgements is greater than their actual performance. Extending beyond a range of contributing factors in the emergence of the overconfidence bias, the present research examines whether superstition, an under-explored yet important factor, can influence people's perceived level of confidence. Drawing on previous findings regarding the consequences of superstitions, we propose that activating the good-luck-related superstitions can increase overconfidence in one's judgment. Specifically, Experiments 1 and 2 show that Chinese Han student and non-student participants, who were activated by different types of superstitions, displayed a higher level of overconfidence than those in the absence of superstition. Experiment 3 fully replicated the causal effect of superstition beliefs on the heightened overconfidence bias in a traditional population of Chinese Qiang people. Moreover, Experiments 1 through 3 consistently show that self-efficacy mediates the relationship between superstition and overconfidence. Taken together, these findings suggest that superstition strengthens people's belief in their own performance ability, which in turn boosts overconfidence.